(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
The findings of the present study had demonstrated that the plant extract possess anti-virucidal and anti-microbial activities according to standard screening tests and conventional accepted protocols. The results indicated that high yield of the extract was obtained at the end of the ethanol soxhlet extraction with the extract having greenish and smoothly textures. The phytochemical screening of methanolic and ethanolic extracts of Allium Sativum bulbs using soxhlet extraction method revealed the presence of tnnins, saponins and steroids in all the extracts. Flavonoid was present in ethanolic extract while alkaloid was present in methanolic extract. The results further revealed that SPyogenes was the most sensitive to the isolated compound while E. Coli was the least Kpneumonia showed high sensitivity to the isolated compound. The low concentration range for the MIC (2.1-uglml-4.0 uglml) and the MBC (2.uglml-18uglml) generally exhibited marked anti-bacterial activities and anti-virucidal potential against the susceptible organisms.